Case Report: Late-Onset Congenital Adrenal Hyperplasia and Acute Covid-19 Infection in a Pregnant Woman: Multidisciplinary Management - Giavoli, Claudia; Iurlaro, Enrico; Morelli, Valentina; Rodari, Giulia; Ronchi, Andrea; Pietrasanta, Carlo; Pugni, Lorenza; Tubiolo, Daniela; Properzi, Paolo; Pesenti, Antonio; Mantovani, Giovanna; Ferrazzi, Enrico; et al. (Frontiers in Endocrinology, 2021)
Background. The impact of the Covid-19 infection on patients with chronic endocrine disease is not fully known. We describe here the first case of a pregnant woman with Covid-19 acute infection and non-classical congenital adrenal hyperplasia (NCAH). Case description. A woman at 36 weeks of gestation referred to our Maternity Hospital for premature rupture of membranes (PROM). Her medical history was positive for NCAH on chronic steroid replacement till the age of 17 years (cortisone acetate and dexamethasone, both in the morning). At admission, her naso-oro-pharyngeal swab resulted positive for SARS-CoV-2. Due to hyperpyrexia and late preterm PROM, caesarean section was planned, and she was started on a 100 mg-bolus of hydrocortisone, followed by continuous infusion of 200 mg/24 hours. A female neonate in good clinical condition and with a negative nasopharyngeal Covid-19 swab was delivered. On second post-partum day, the mother was in good conditions and was switched to oral steroid therapy. On third post-partum day she worsened, with radiological signs of acute pulmonary embolism. Oro-tracheal intubation and mechanical ventilation were started and she was switched back to intravenous steroid therapy. On April 30, pulmonary embolism was resolved and on May 13th she was discharged in good conditions. Conclusions. We report the first case of Covid-19 acute infection occurred in late-pregnancy in a woman with NCAH on chronic steroid replacement. The management of the patient in a reference Centre with early involvement of a multidisciplinary team granted prompt care and adequate protection for all the involved sanitary operators.